Abatacept/ruxolitinib and screening for concomitant respiratory muscle failure to mitigate fatality of immune-checkpoint inhibitor myocarditis - Salem, Joe-Elie; Bretagne, Marie; Abbar, Baptiste; Lehmann, Lorenz (Cancer discovery, 2023)
Immune-checkpoint-inhibitor (ICI)-associated myotoxicity involves the heart (myocarditis) and skeletal muscles (myositis), which frequently occur concurrently and are highly fatal. We report the results of a strategy that included identification of individuals with severe ICI myocarditis by also screening for and managing concomitant respiratory muscle involvement with mechanical ventilation, as well as treatment with the CTLA4 fusion protein abatacept and the JAK inhibitor ruxolitinib. Forty cases with definite ICI myocarditis were included with pathologic confirmation of concomitant myositis in the majority of patients. In the first 10 patients, using recommended guidelines, myotoxicity-related fatality occurred in 60%, consistent with historical controls. In the subsequent 30 cases, we instituted systematic screening for respiratory muscle involvement coupled with active ventilation and treatment using ruxolitinib and abatacept. The abatacept dose was adjusted using CD86 receptor occupancy on circulating monocytes. The myotoxicity-related fatality rate was 3.4% (1/30) in these 30 patients versus 60% in the first quartile (P < 0.0001). These clinical results are hypothesis-generating and need further evaluation.Early management of respiratory muscle failure using mechanical ventilation and high-dose abatacept with CD86 receptor occupancy monitoring combined with ruxolitinib may be promising to mitigate high fatality rates in severe ICI myocarditis.See related commentary by Dougan, p. 1040.This article is highlighted in the In This Issue feature, p. 1027
Gesehen am 21.11.2023